2021
DOI: 10.1108/bfj-06-2020-0501
|View full text |Cite
|
Sign up to set email alerts
|

Multiobjective optimization of the flaxseed mucilage extraction process using normal-boundary intersection approach

Abstract: PurposeThe mucilage of the Linum usitatissimum L. seed (Linseed) is one of the natural mucilages that presents a great potential to provide a food hydrocolloid with potential applications in both food and pharmaceutical industries. To increase the yield and quality of linseed oil during its production process, it is necessary to previously extract its polysaccharides. Because of this, flax mucilage production can be made viable as a byproduct of oil extraction process, which is already a product of high commer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Therefore, it is necessary to identify the correct approximation to represent these responses as functions of these variables. For this purpose, polynomial functions are used [36]. Multivariate regression models (generated in Matlab R2021a) were used to perform ultrasound-assisted extraction optimization.…”
Section: Mathematical Modelmentioning
confidence: 99%
“…Therefore, it is necessary to identify the correct approximation to represent these responses as functions of these variables. For this purpose, polynomial functions are used [36]. Multivariate regression models (generated in Matlab R2021a) were used to perform ultrasound-assisted extraction optimization.…”
Section: Mathematical Modelmentioning
confidence: 99%
“…Brown flaxseeds were purchased from a local market in Niterói City, Rio de Janeiro, Brazil. The simplified mucilage extraction procedure was based on the works of Ziolkovska (2012), Cui et al (1994), andRocha et al (2021b); it consisted of washing the whole seeds with distilled water, in a ratio of 1:13 m/v (seeds:water) at room temperature, with mechanical agitation of around 500 rotations per minute (RPM) (IKA Labortechnik RW 20DZM.n). The duration of the washing process was 24 h. Afterwards, the aqueous extract was filtered through regular, double-layered medical gauze to separate it from the seeds and subsequently lyophilized (LIOTOP L108) at -50 °C for 5 uninterrupted days.…”
Section: Mucilage Extraction and Dryingmentioning
confidence: 99%
“…In another study, Ziolkovska [ 16 ] showed >99% extraction of water-soluble substances from the hull of whole flaxseed via the application of a three-stage countercurrent extraction process under the following conditions: a seed-to-water ratio of 1:25, a temperature of 80 ± 2 °C, and a duration of 30 ± 1 min (each stage). Rocha et al [ 17 ] used a multi-objective optimization (MOO) method, namely, the normal boundary intersection (NBI), for FM extraction. They showed that, to obtain the highest fiber concentration in the extract, the optimal extraction conditions were a temperature of 46 °C, a pH of 3.81, and a time of 13.46 h; to obtain the maximum extraction yield, the optimal extraction conditions were a temperature of 65 °C, a pH of 6.45, and a time of 14.41 h.…”
Section: Extraction Of Mucilagementioning
confidence: 99%